Forecasting the cumulative number of COVID-19 deaths in China: a Boltzmann function-based modeling study. (2nd July 2020) - Gao, Yuanyuan; Zhang, Zuqin; Yao, Wei; Ying, Qi; Long, Cheng; Fu, Xinmiao
Abstract: The COVID-19 outbreak is ongoing in China. Here, Boltzmann function-based analyses reveal the potential total numbers of COVID-19 deaths: 3, 260 (95% confidence interval [CI], 3187–3394) in China; 110 (95% CI, 109–112) in Hubei Province; 3, 174 (95% CI, 3095–3270) outside Hubei; 2, 550 (95% CI, 2494–2621) in Wuhan City; and 617 (95% CI, 607–632) outside Wuhan.